Three-dimensional Assessment of Longitudinal Surgical Outcome in Patients with Unilateral Cleft Lip and Palate: A Modified Rotation Advancement Technique - Xu, Yulang; Yao, Meilin; Shi, Bing; Li, Jingtao; Zheng, Qian; Zeng, Ni (Clinical oral investigations, 2024)
Background Optimization of a modified rotation advancement technique is hampered by lack of objective measures to quantify the longitudinal surgical outcome. Methods We collected and assessed facial 3D images of 115 consecutive patients who underwent primary repair between 2017 and 2019. Photogrammetry was performed preoperatively, immediately postoperatively and at a first and second follow-up interval, occurring at an average year of 0.6 and 5.3 years, respectively. 10 additional age-matched noncleft control subjects were also included. Results Growth lag in cleft side lateral lip and gradual elongation of medial lip height on the cleft side caused continuous deviation of philtrum towards the cleft side. The columellar length on the cleft side continued to grow slower, accompanied by a persistent widening of alar base width on the cleft side, leading to in the gradual deviation of columella towards the cleft side. The pre-operative and post-operative nasolabial asymmetry would increase with greater degree of postoperative deficiencies. Right clefts presented with greater degrees of deficiencies in lateral lip height in preoperative measurement, but this discrepancy of the laterality of clefts was not observed in the two follow-up periods. Conclusion The surgical outcome of this modified rotational advancement technique in unilateral cleft lip primary repair is promising. Growth lag in lateral lip and lateral displacement of alar base cause continuous deviation of philtrum towards the cleft side. Pre-operative severity does predict post-operative outcomes. Laterality of oral clefts does not significantly affect the long-term outcomes of surgery. Practical implication This surgical technique meets the current trend of cleft lip and palate primary repair and is worth promoting.